Theodor Storms Erstlingsnovelle «Marthe und ihre Uhr» (1847) (Studia theodisca, 2013)
This article intends to fill the previous void of a thorough critical assessment and interpretive analysis of Theodor Storm’s first novellistic, albeit concise narrative of 1847. As an aesthetic and highly symbolic story, Marthe’s seemingly timeless table clock bears some striking affinities with Eduard Mörike’s objet d’art of 1838, his «Lampe». As an ardent admirer of his contemporary Mörike, Storm here lays his theoretical and artistic foundations for his major novellas of later years.